2006
DOI: 10.1007/s00431-006-0182-4
|View full text |Cite
|
Sign up to set email alerts
|

Growth hormone impaired secretion and antipituitary antibodies in patients with coeliac disease and poor catch-up growth after a long gluten-free diet period: a causal association?

Abstract: In our study, the presence of APA in CD children without catch-up growth after GFD seems to be able to identify an autoimmune form of hypophysitis involving the somatotrophs cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 47 publications
2
18
2
1
Order By: Relevance
“…We characterized APA in adults and prepubertal children with idiopathic GHD [70][71][72], in children with coeliac disease with a lack of catch-up growth after a gluten-free diet [73] and, recently, in male adults with idiopathic hypogonadotropic hypogonadism [74]. APA against somatotrophs or gonadotrophs, when present at high titres, may be considered a good diagnostic marker of autoimmune forms of GHD and gonadotropin deficiency respectively.…”
Section: Role Of Apa In Lyhmentioning
confidence: 98%
“…We characterized APA in adults and prepubertal children with idiopathic GHD [70][71][72], in children with coeliac disease with a lack of catch-up growth after a gluten-free diet [73] and, recently, in male adults with idiopathic hypogonadotropic hypogonadism [74]. APA against somatotrophs or gonadotrophs, when present at high titres, may be considered a good diagnostic marker of autoimmune forms of GHD and gonadotropin deficiency respectively.…”
Section: Role Of Apa In Lyhmentioning
confidence: 98%
“…As in previous studies, other factors such as degree of mucosal damage, symptoms and gender do not have any impact on weight and height gain [11]. Additionally, it was shown that autoimmune hypophysitis may be responsible for the poor catch-up growth after gluten-free diet [12].…”
Section: Discussionmentioning
confidence: 91%
“…22 Other studies emphasize on antipituitary autoantibodies (APA) as a case of autoimmune hypophysitis in the somatotroph cells. 24 …”
Section: Discussionmentioning
confidence: 99%